Exosomes in Intestinal Inflammation - Ayyar, Kanchana K.; Moss, Alan C. (Frontiers in Pharmacology, 2021)
Exosomes are 30-150nm sized vesicles produced by cells to facilitate intercellular transport and signaling. Exosomes may carry different cargo including nucleic acids, proteins and lipids. Exosomes can be released by a variety of cells and are found in most physiological fluids (blood, urine, saliva, breast milk). Inflammatory Bowel Disease (IBD) is a consequence of a dysregulated mucosal immune system, and can lead to several complications. Current methods of diagnosing and monitoring IBD are invasive, time-consuming, and lack specificity for inflammatory pathways. Exosomes are released by inflamed intestinal epithelial cells which can be captured in blood, urine or feces, with potential as non-invasive biomarkers in IBD. This review aims to understand the exosome profile in humans and other mammals, the cargo contained in them, the effect of exosomes on the gut, and the potential use of exosomes in therapy.